ICDSSI 2015 – THE BEST PLATFORM TO EXPLORE ISSUES ON SOCIO-SPATIAL INEQUALITY - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, August 2015 – A nation may not be considered as being fully developed if the progress and development are not equally distributed among its citizens of different levels of society especially in the context of social space.